Mexico : IAIS Insurance Core Principles - Detailed Assessment of Observance - International Monetary Fund; World Bank (World Bank, Washington, Dc, 2014)
This is a full assessment of the insurance regulatory and supervisory system in Mexico, to ascertain its compliance with the IAIS core principles, as a part of the Financial Sector Assessment Program (FSAP) in September 2011. This assessment was produced in the course of a joint International Monetary Fund (IMF), World Bank mission in Mexico to conduct an update of the IAIS principles under the FSAP. The recommendations after conclusion of the assessment include developing and implementing a comprehensive plan to increase insurance penetration; ensuring the operational independence and continuity of the Insurance and Surety National Commission (CNSF); confirming that the supervisory authority has full discretion on resource allocation, in accordance to its mandate, objectives, and the perceived risks; establishing an implementation plan on the solvency regime; and revisiting the arbitration mechanism. This document presents a detailed assessment with regard to the twenty-eight IAIS principles, examining the system in context of each principle.